Agronomic performance and genetic variability in kale genotypes - Azevedo, Alcinei Mistico; Andrade Júnior, Valter Carvalho de; Pedrosa, Carlos Enrrik; Fernandes, José Sebastião Cunha; Valadares, Nermy Ribeiro; Ferreira, Marcos Aurélio Miranda; Martins, Rafael Augusto do Valle (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the agronomic performance of kale genotypes and to estimate the genetic parameters and the correlation between traits of interest for breeding. The experiment was carried out in a randomized block design, with 30 kale genotypes, with three commercial cultivars, from three different companies. It was used four replicates, with five individuals per plot. Variability was significant among genotypes, with predominance of genetic effects over environmental ones, indicating the possibility of obtaining expressive genetic gains in breeding. The most important traits for breeding purposes were: leaf length and width, stem diameter, leaf area, plant height, number of shoots, and leaf dry weight. Commercial genotypes showed smaller leaf area, dry leaf mass, plant height, leaf length and width, petiole length, and number of sprouts and commercial leaves.